Detecting zombie banks - Fiordelisi, Franco; Radić, Nemanja; Weyman-Jones, Thomas (Taylor and Francis, 2021)
Capital adequacy has become the main regulatory tool to achieve financial stability in the last twenty years. While most papers analysed the effect of capital adequacy on risk taking, there is a lack of evidence on the relationship between deleveraging and the return on equity capital. In this paper, we examine the evolution of the banking system in Japan over the period 2000–16, where the re-capitalization issue has already played a major role in policy making. Specifically, we estimate the shadow return on equity capital for both listed and unlisted banks by measuring the loans-funding-equity technology through the dual cost function, controlling for risk exposure and bad loans, and accounting for both the standard asset-based model of bank outputs, and income-based model. Such an approach is likely to be important if the central bank permits banks with unsustainable balance sheets to continue in existence, and we refer to this as zombie banking. Overall, our results show that deleveraging did reduce the shadow return on equity for the City banks. We also find that that the presence of ‘zombie’ banks was concentrated and large among the smaller less diversified Regional Banks.
Keywords: Bank cost function; shadow return on equity; panel data estimation